2023
DOI: 10.3390/molecules28020901
|View full text |Cite
|
Sign up to set email alerts
|

Plant Essential Oils as Healthy Functional Ingredients of Nutraceuticals and Diet Supplements: A Review

Abstract: Essential oils (EOs) are mixtures of volatile molecules endowed with health-promoting biological activities that go beyond their role as aromas and natural preservatives and can be exploited to develop functional foods and diet supplements. Their composition is briefly addressed along with regulatory aspects. The potential health benefit of human diet supplementation with EOs is outlined through a review of the recent literature on available clinical trials and preclinical research concerning EOs activity towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 171 publications
(246 reference statements)
0
23
1
Order By: Relevance
“…Characteristically, in the review article from Pastor et al about the beneficial effects of dietary supplementation with olive oil, oleic acid or HT in metabolic syndrome, the authors identified only four eligible studies that met their search criteria [ 40 ]. The abundance of EOs also limits the extensive and in-depth investigation of specific EOs on specific health conditions and/or risk factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically, in the review article from Pastor et al about the beneficial effects of dietary supplementation with olive oil, oleic acid or HT in metabolic syndrome, the authors identified only four eligible studies that met their search criteria [ 40 ]. The abundance of EOs also limits the extensive and in-depth investigation of specific EOs on specific health conditions and/or risk factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, the in poration of essential oils into foods is in line with green consumerism and allows for use of clean labels on foods, making them a very tempting raw material for the food sec Around 300 essential oils have been marketed in flavor and fragrance products with the main trade oils attaining over 1000 t/year. The essential oils most commonly used in food products include anise, basil, bergamot, chamomile, green and black cumin, coriander, garlic, lavender, lemon, lemon balm, myrtle, neroli, rosemary, orange, peppermint, pine, thyme and yarrow, as recently reviewed [15]. The global flavors and fragrances market is expected to grow with a very recent report predicting an increase of up to USD 44.6 billion by 2030.…”
Section: Overview On Aromatic Plants and Their Volatile Extractsmentioning
confidence: 99%
“…[25][26][27] In addition, essential oils have been shown to stimulate the digestive process and metabolism, thereby improving metabolic disorders. [28][29][30] The small, spherical, and often simple-to-peel, C. reticulata fruit has a sweet, juicy pulp that is high in vitamin C and other healthy compounds. [31] The peel of C. reticulata is often discarded after its use, which can be used for the extraction of essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus essential oils also contain high levels of antioxidants, which can help protect the body from oxidative damage caused by free radicals [25–27] . In addition, essential oils have been shown to stimulate the digestive process and metabolism, thereby improving metabolic disorders [28–30] …”
Section: Introductionmentioning
confidence: 99%